2021
DOI: 10.3390/electronics10060699
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Supervised Machine Learning Classifier System for Breast Cancer Prognosis Using Feature Selection and Data Imbalance Handling Approaches

Abstract: Nowadays, breast cancer is the most frequent cancer among women. Early detection is a critical issue that can be effectively achieved by machine learning (ML) techniques. Thus in this article, the methods to improve the accuracy of ML classification models for the prognosis of breast cancer are investigated. Wrapper-based feature selection approach along with nature-inspired algorithms such as Particle Swarm Optimization, Genetic Search, and Greedy Stepwise has been used to identify the important features. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Solanki et al also investigated the prediction of benign or malignant BC using selected ML techniques. The results showed that the J-48 yielded the best classification performance with an accuracy of 98.83% (49).…”
Section: Discussionmentioning
confidence: 99%
“…Solanki et al also investigated the prediction of benign or malignant BC using selected ML techniques. The results showed that the J-48 yielded the best classification performance with an accuracy of 98.83% (49).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the over-sampling method is based on SMOTE. It has been widely used as a baseline over-sampling method for breast cancer datasets [14][15][16][17]. The percentage of synthetic instances was set to make the two datasets become balanced datasets where the malignant and benign classes contain the same numbers of data samples.…”
Section: The Feature Selection and Over-sampling Methodsmentioning
confidence: 99%
“…According to Fernandez et al [16], SMOTE over-sampling can benefit from the use of feature selection, where feature selection is performed over the class imbalanced dataset to select a subset feature of it, and then the reduced dataset is over-sampled to make it contain the same size of the data samples as in the majority and minority classes. Recently, Solanki et al [17] propose the contrary procedure that SMOTE be performed first to rebalance the breast cancer dataset, and then wrapper-based feature selection methods can be applied to reduce the feature dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) has achieved very good results for prediction and timely treatment of various diseases [22,23]. For instance, Solanki et al [24], proposed methods for improving the performance of ML classification models, namely a support vector machine (SVM), a decision tree, and a multilayer perceptron (MLP), i.e., a feed-forward artificial neural network (ANN), for the prognosis of breast cancer. ML models can be utilized also to predict blood glucose levels, based on collected medical data and various human body's health indicators.…”
Section: Related Workmentioning
confidence: 99%